Prevalence of oral soft tissue lesions in alcohol and tobacco users in slums of Jammu city - Sumbria, Deepshikha; Hamid, Waqar Ul; Yousuf, Aamir; Ahmad, Rauf (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: There is a range of negative consequences on the oral mucosa caused by the tobacco and alcohol from inceptive light mucosal changes to a full-blown malignancy. The purpose of this study was to assess the risk of oral lesions resulting from the habits of addiction and prevalence of oral soft tissues changes with alcohol consumption, smoking, chewing and both type habits in individual residing in slums. Methods: This cross-sectional study was carried out in the slums of Jammu city. A questionnaire was used to obtain the information on substance abuse habits followed by oral clinical examination in selected population of 1200 individuals >15 years of age. The data collected were statistically analysed using chi-square test. Results: Of the 1200 study population, 816 were males and 384 were females and 72% were addicted to one or the other form of tobacco and alcohol. 32.6% showed oral mucosal changes, out of these, smoker’s melanosis was found in 10.4%, leukoplakia in 9.1%, oral submucus fibrosis in 6.6%, oral lichen planus in 2.8%, chewer’s mucosa in 2%, lichenoid oral lesion in 1.2%, erythroplakia in 0.5%. Conclusions: The increased production and use of tobacco in India have led to increased prevalence of oral mucosal lesions. Community preventive and control programmes should be aimed at high risk individuals based on the epidemiological data gathered through such studies to reduce the burden of illness caused due to substance abuse.